Calvin dan Penafsiran Kitab Suci - Bernard Aubert (STT Reformed Injili Internasional, 2022)
This article examines John Calvin’s (1509–1564) method of biblical interpretation. It first considers his approach in the context of the history of interpretation and then examines two examples of his method of interpretation of Psalm 2 and Acts 20:17–38. It will be suggested that Calvin’s approach can enrich the renewal of interest in theological interpretation in the academy and the church. Although some traits of Calvin’s interpretation resemble modern approaches, this essay confirms the shift in Calvin studies that classify his method as a type of precritical interpretation—in particular, Calvin’s concern for application, his use of the analogy of faith, and his integration of exegesis and doctrine.